P-Ca, AG4/7 and 6-BAP in the physiology and nutrition of tomato in the greenhouse - Ramírez, Homero; López-Fabian, Abdiel; Peña-Cervantes, Edmundo; Zavala-Ramírez, María Guadalupe; Zermeño-Gónzalez, Alejandro (Revista Mexicana de Ciencias Agrícolas, 2018)
The tomato is a crop of worldwide importance for its contribution in labor, economy and food quality. These characteristics require a continuous search for technologies that contribute to improving fruit yield and quality. In this study, the effect of bioregulators on foliar parameters, nutrient content, yield and fruit quality was evaluated in hybrid saladette tomato “Raptor-F1” at the UAAAN, Saltillo, Coahuila, during April-august 2015, under greenhouse conditions. When the plants showed floral primordia, a first foliar application was made with manual spray at the dew point of the treatments: control (water), P-Ca (50 mg L-1), AG4/7 (50 mg L-1), AG4/7 (100 mg L-1), 6-BAP (50 mg L-1), 6-BAP (100 mg L-1), AG4/7 (50 mg L-1)+6-BAP (50 mg L-1) and AG4/7 (100 mg L-1)+6-BAP (100 mg L-1) and 15 days later, a second application of the same doses was performed. A completely randomized statistical design with ten repetitions per treatment was established. The results were analyzed using the DMS test (p≤ 0.05). P-Ca and 6-BAP at 50 mg L-1 did not modify the foliar parameters and yield per plant; however, they increased the level of potassium in leaves and nitrogen and calcium in fruits. 6-BAP at 50 mg L-1 increased the fresh and dry matter, while when combined with gibberellin AG4/7 at 100 mg L-1 increased the vitamin C and lycopene content in fruits. It is concluded that the individual or combined concentrations of P-Ca, AG4/7 and 6-BAP, favor the quality of hybrid tomato “Raptor-F1” saladette in the greenhouse.